Distinctive Characteristics of Small Businesses as Sites for Informal Learning. (June 2017) - Coetzer, Alan; Kock, Henrik; Wallo, Andreas
Few studies have examined workplace factors that influence informal learning in small businesses and in general the studies are not framed by the characteristics of small businesses. To address this weakness in existing literature, we conducted a review of literatures which examine (a) workplace factors that influence informal learning, (b) small-business characteristics, and (c) factors influencing informal learning in small businesses. The several workplace factors that influence learning were categorized as job and relational and organizational characteristics. Each category was examined in relation to characteristics of small businesses. We outline what is known about each category and what we need to learn about them as they relate to informal learning in small businesses. For each category, propositions are generated that should be examined in future research. We also produce a heuristic conceptual framework that can be used to focus and bound future research that tests a different set of propositions.